Rheological and mechanical properties of edible gel materials for 3D food printing technology - Rahman, Julkarnyne M. Habibur; Shiblee, MD Nahin Islam; Ahmed, Kumkum; Khosla, Ajit; Kawakami, Masaru; Furukawa, Hidemitsu (Heliyon, 2020)
3D food printing sectors require comprehensive knowledge on viscoelastic and mechanical properties of diverse food materials in order to effectively utilize them in rapid and customized 3D production for supply and manufacturing chains. In this work, we present mechanical and rheological properties of Agar and Konjac based edible gels at different Agar and Konjac weight ratio and discuss their 3D printing performance. Gel samples with higher Konjac content positively contributed to the viscoelastic properties of the gel samples which in return has been found viable for extrusion-based 3D printing. By choosing appropriate printing parameters, different shapes are printed to demonstrate printing resolution. We expect, this study will add potential scope for evaluating and optimizing soft-gel materials for 3D food printing sector. 3D printing, Rheology, Mechanical properties, Edible gel, Food printing